2016
DOI: 10.2147/ott.s108580
|View full text |Cite
|
Sign up to set email alerts
|

Weekly nanoparticle albumin bound-paclitaxel in combination with cisplatin versus weekly solvent-based paclitaxel plus cisplatin as first-line therapy in Chinese patients with advanced esophageal squamous cell carcinoma

Abstract: ObjectiveMore effective regimens for advanced esophageal squamous cell carcinoma (ESCC) are urgently needed. Therefore, a retrospective study concerning the efficacy and safety of nanoparticle albumin-bound paclitaxel plus cisplatin (nab-TP) versus solvent-based paclitaxel plus cisplatin (sb-TP) as a first-line therapy was conducted in Chinese patients with advanced ESCC.MethodsFrom June 2009 to June 2015, 32 patients were treated with nab-paclitaxel (125 mg/m2) on the first and eighth days (30 minutes infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Abraxane is a unique nanoparticle of an albumin‐bound form of paclitaxel, which has a higher response rate and enhanced safety profiles compared to a solvent‐based formulation of paclitaxel. 18 , 19 Abraxane is associated with a prolonged half‐life, increased accumulation in the tumour, macropinocytosis‐driven activation of macrophages, apoptosis of cancer cells and improved accessibility for immune cells and therapeutics to the TME through stromal depletion. 20 The treatment of Abraxane combined with gemcitabine was granted FDA approval in 2013 for patients with late‐stage pancreatic cancer, based on the results of a phase III randomized trial, which demonstrated that Abraxane/gemcitabine provides a significantly improved median overall survival of 8.5 months, compared to 6.7 months for gemcitabine alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abraxane is a unique nanoparticle of an albumin‐bound form of paclitaxel, which has a higher response rate and enhanced safety profiles compared to a solvent‐based formulation of paclitaxel. 18 , 19 Abraxane is associated with a prolonged half‐life, increased accumulation in the tumour, macropinocytosis‐driven activation of macrophages, apoptosis of cancer cells and improved accessibility for immune cells and therapeutics to the TME through stromal depletion. 20 The treatment of Abraxane combined with gemcitabine was granted FDA approval in 2013 for patients with late‐stage pancreatic cancer, based on the results of a phase III randomized trial, which demonstrated that Abraxane/gemcitabine provides a significantly improved median overall survival of 8.5 months, compared to 6.7 months for gemcitabine alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the serious adverse effects mean that FOLFIRINOX is only suitable for PDAC patients with a relatively good performance status. Abraxane is a unique nanoparticle of an albumin‐bound form of paclitaxel, which has a higher response rate and enhanced safety profiles compared to a solvent‐based formulation of paclitaxel 18,19 . Abraxane is associated with a prolonged half‐life, increased accumulation in the tumour, macropinocytosis‐driven activation of macrophages, apoptosis of cancer cells and improved accessibility for immune cells and therapeutics to the TME through stromal depletion 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 13 ] demonstrated that weekly nab-paclitaxel plus cisplatin with concurrent definitive radiotherapy is an effective and well-tolerated treatment option for ESCC. In addition, Wang et al [ 14 ] compared the values of nanoparticle albumin-bound paclitaxel plus cisplatin (nab-TP) vs solvent-based paclitaxel plus cisplatin (sb-TP) and found that nab-TP demonstrated a higher ORR (50% vs 30%, P = 0.082) and disease control rate (81% vs 65%, P = 0.124) than sb-TP, as well as a longer median PFS (6.1 mo, 95%CI: 5.3-6.9) ( P = 0.029). In contrast, LBP used in our current study is a new-generation platinum drug.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 , 24 , 25 Particularly for advanced ESCC cases, nabTP as a first‐line therapy may improve survival with an increased response rate. 26 In addition, nab‐paclitaxel based neoadjuvant chemotherapy has been shown to produce positive results for locally advanced ESCC. 27 Nevertheless, the comparison of nabTP‐ICIs and TP‐ICIs schemes is still lacking.…”
Section: Introductionmentioning
confidence: 99%